Does Social Capital Matter for the Development of Scheduled Tribes in Kerala? An Inter-tribal Analysis - U, Balakrishnan; K, Hari Kurup K. (Review of Development and Change, 2024)
The study intends to explore and substantiate the effectiveness of social capital in the development of different tribes in Kerala, specifically examining inter-tribal disparities. Primary data were gathered from the Kasaragod district in Kerala, encompas
Keywords: Bonding; Bridging; Inter-Tribal Analysis; Scheduled Tribes; Social Capital